Use of small-scale liquefaction features to assess paleoseismicity: an example from the Saline River fault zone, Southeast Arkansas, USA - Cox, Randel T.; Lowe, Christopher; Hao, Yanjun; Mahan, Shannon A. (Frontiers in Earth Science, 2014)
Large-scale liquefaction features (e.g., sand blows, lateral-spread fissure vents) that can be recognized on remote-sensing imagery and photography have been of great utility in developing chronologies of paleo-earthquakes. In areas where large-scale features are obscured on imagery by forest cover and Holocene exposure is lacking, small-scale liquefaction features (e.g., convoluted bedding, clastic intrusions, foundered and suspended blocks, water-escape structures) offer an alternative data source that can be investigated in meter-scale excavations. In order to assess the geographic extent of Holocene sand blow fields in southeast Arkansas that were previously mapped on river terraces and flood plains using aerial photography, we investigated the distribution of small-scale liquefaction features in alluvium along streams within a forested region between the sand blow fields. Our results suggest that the fields are not continuous and do not reflect a single large liquefaction field related to paleo-earthquakes >M 6.5. Features at one of our sites suggests the Desha County sand blow field may be larger than presently mapped, and that the distance from the center of the field to the farthest liquefaction may be ~30 km. The empirical relationship of magnitude and distance to farthest liquefaction suggests a field of this size could have been produced by a M 6.3 earthquake. We also found Holocene liquefaction features that we interpret as resulting from ground shaking near previously documented Pleistocene and Holocene surface ruptures of the Saline River fault zone. Liquefaction during a paleo-earthquake (~M 5.5) may have coincided with movement on that fault zone ~AD 1700.